Peningkatan Pemahaman Pengelolaan Obat Keluarga dan Pangan Sehat untuk Anak sebagai Implementasi SDGS 3 di Bojonegoro: Increased Understanding of Family Medicine Management and Healthy Food for Children as Implementation of SDGS 3 in Bojonegoro - Suzana Suzana; Juni Ekowati; I Nyoman Wijaya; Rosita Handayani; Siti Rahmah; Bambang Tri Purwanto; Dewi Melani Hariyadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This service activity is motivated by efforts to maintain health after the Covid-19 pandemic. The community carries out preventive efforts by providing stocks of their medicines at home. The culture of storing medicines in the household requires proper drug management to prevent drug damage due to improper storage, drug use errors, and environmental pollution due to errors in handling damaged or expired drugs. The pharmacist's role is vital in providing drug management education to the community. Another preventive effort undertaken by the community is to maintain a healthy body by applying a diet where fast food currently contains a lot of Food Additives (BTP), which can threaten long-term public health. For this reason, people need to get an education directly, so they are wise in using BTP. The solution is to educate the public regarding managing household medicines and healthy food for parents and guardians of RA Al Manshur Play Group (KB) students in Bojonegoro. Activities are packaged in counseling methods and training/practice activities. The expected outcome of the activity is an increase in the understanding of guardian parents, as indicated by an average post-test score of >65 with an increase in score of >10% compared to the pretest. By increasing the understanding of parents and teachers about managing medicines and healthy food in the family, it is hoped that conditions of good health and well-being in society will be achieved.